Right to Marry - Majstorović, Irena; Šimović, Ivan (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
The right to marry represents a fundamental human right, protected primarily for its significance in founding a family. Family has always been understood as one of the basic values in the life of an individual, but also one of the basic values of society, due to its great contribution in preserving social stability and development. This right is protected by a plethora of global and regional documents, among others the European Convention on the Protection of Human Rights and Fundamental Freedoms (Article 12).It is therefore the aim of this chapter to represent an incentive for further analysis of the right to marry, in light of current trends, and in particular of its limitations, such as the issues of marriageable age, consanguinity, number of spouses, consensus and capacity. The corollary principle of the equality of spouses, as emphasised in Article 5 of the Protocol 7 to the European convention represents a parallel fil rouge, since it is a conditio sine qua non in all considerations regarding marriage. Doctrinary considerations are complemented by references to relevant case law of the European court of human rights, while particular attention is devoted to selected topics with regard to the countries of Central and Eastern Europe, namely religious marriages, the issue of the aim of marriage, and divorce. The conclusion deriving from the analysis is that the cautious approach of the European Court, relying on European-wide consensus, or in other words the Court’s choice to follow, and not to lead, is welcomed. Namely, the issue of marriage is inextricably linked to traditions of the states and the cautious approach should therefore be continued.Keywords: Right to marry and to found a family, Article 12 of the European Convention on Human Rights and Fundamental Freedoms, European Court of Human Rights, family law